Effect of residual H2O2 from advanced oxidation processes on subsequent biological water treatment: A laboratory batch study. (October 2017) - Wang, Feifei; van Halem, Doris; Liu, Gang; Lekkerkerker-Teunissen, Karin; van der Hoek, Jan Peter
Abstract: H2 O2 residuals from advanced oxidation processes (AOPs) may have critical impacts on the microbial ecology and performance of subsequent biological treatment processes, but little is known. The objective of this study was to evaluate how H2 O2 residuals influence sand systems with an emphasis on dissolved organic carbon (DOC) removal, microbial activity change and bacterial community evolution. The results from laboratory batch studies showed that 0.25 mg/L H2 O2 lowered DOC removal by 10% while higher H2 O2 concentrations at 3 and 5 mg/L promoted DOC removal by 8% and 28%. A H2 O2 dosage of 0.25 mg/L did not impact microbial activity (as measured by ATP) while high H2 O2 dosages, 1, 3 and 5 mg/L, resulted in reduced microbial activity of 23%, 37% and 37% respectively. Therefore, DOC removal was promoted by the increase of H2 O2 dosage while microbial activity was reduced. The pyrosequencing results illustrated that bacterial communities were dominated by Proteobacteria . The presence of H2 O2 showed clear influence on the diversity and composition of bacterial communities, which became more diverse under 0.25 mg/L H2 O2 but conversely less diverse when the dosage increased to 5 mg/L H2 O2 . Anaerobic bacteria were found to be most sensitive to H2 O2 as their growth in batch reactors was limited by both 0.25 and 5 mg/L H2 O2 (17–88% reduction). In conclusion, special attention should be given to effects of AOPs residuals on microbial ecology before introducing AOPs as a pre-treatment to biological (sand) processes. Additionally, the guideline on the maximum allowable H2 O2 concentration should be properly evaluated. Graphical abstract: Highlights: The effect of H2 O2 on sand systems during water treatment was studied as the first time. DOC biodegradation was limited by 0.25 mg/L H2 O2 and promoted by 5 mg/L H2 O2 . Microbial activity decreased with the increase of H2 O2 concentrations. Aerobic bacteria showed different responses to H2 O2, either sensitive or tolerant. Anaerobic bacteria are sensitive to H2 O2 . Their growth was limited by H2 O2 .